Hitting the Trillion Mark : A Look at How Much Countries Are Spending on Infrastructure - Fay, Marianne; Lee, Hyoung Il; Mastruzzi, Massimo; Han, Sungmin; Cho, Moonkyoung (World Bank, Washington, DC, 2019)
The paper provides the first consistently estimated data set on infrastructure investments in low- and middle-income countries. To do so, the authors identify three possible proxies for infrastructure investments: two are variants on gross fixed capital formation from national accounts system data following ADB (2017) and one is based on fiscal data from the World Bank's BOOST database. Two of these proxies rely on the World Bank's Private Participation in Infrastructure database to capture the private share of infrastructure investments. Given the limitations of each of these proxies, the authors employ several transformations to derive a lower-bound estimate for infrastructure investments in low-and middle-income countries of 3.40 percent of their gross domestic product, a central estimate of around 4 percent, and an upper-bound estimate of 5 percent for 2011. Corresponding absolute amounts are US$0.82 trillion, US$1.00 trillion, and US$1.21 trillion, respectively with East Asia and the Pacific accounting for 55 percent of infrastructure investments and Africa 4 percent. The public sector largely dominates infrastructure spending, accounting for 87–91 percent of infrastructure investments, but with wide variation across regions, from a low of 53–64 percent in South Asia to a high of 98 percent in East Asia. Given the absence of fiscal or national accounts data capturing investments in infrastructure, these estimates are likely to be the best available in the near future. Nevertheless, the authors propose some possible avenues for future improvements (including an update when 2017 data are made available by the International Comparison Project), building on the excellent collaboration of multilateral development banks around this issue.